Broken symmetry states of metallacrowns: Distribution of spins and the g tensor - Pavlyukh, Yaroslav; Rentschler, Eva; Elmers, H. J.; Huebner, W.; Lefkidis, Georg (Physical Review B, 2019)
In this work we focus on the magnetic properties of metallacrown complexes as computed by various density functional methods. Using the broken symmetry approach, we determine the exchange-coupling constants and the g tensors and compare them with experimentally determined ones from the temperature-dependent magnetic susceptibilities and by the electronic spin resonance, respectively. Generalization of the Noodleman-Dai-Whangbo approach for systems with multiple magnetic centers that we introduce here allows to make quantitative statements about the nature of these electronic states in density functional theory.
CRIS-Team Scopus Importer:2023-03-27